A long-lived peptide-conjugated iridium(iii) complex as a luminescent probe and inhibitor of the cell migration mediator, formyl peptide receptor 2. Issue 43 (8th October 2018) - Vellaisamy, Kasipandi; Li, Guodong; Wang, Wanhe; Leung, Chung-Hang; Ma, Dik-Lung
Abstract : Formyl peptide receptors play important biological and therapeutic roles in wound repair and inflammatory diseases. Abstract : Formyl peptide receptors play important biological and therapeutic roles in wound repair and inflammatory diseases. In this work, we present a luminescent iridium(iii ) complex (6 ) conjugated with the peptide agonist WKYMVm as a luminescent formyl peptide receptor 2 (FPR2) imaging probe in living cells. Complex6 displayed ideal cell imaging characteristics, high photostability and low cytotoxicity. Competition assays with a known FPR2 antagonist, WRW4, and siRNA knockdown experiments both revealed that complex6 selectively targeted FPR2 in living HUVEC cells. Moreover, complex6 regulated FPR2 signalling in HUVEC cells as shown using a mechanical scratch assay. Finally, complex6 reduced epithelial cell migration capacity and inhibited lipoxin A4 (LXA4)-triggered cell migration in HUVEC cells, demonstrating the ability of this complex to inhibit FPR2 in living cells. To our knowledge, this is the first long-lived probe for imaging FPR2 in living cells.